A CASE REPORT ON GLYPHOSATE POISONING - CHAKRABORTY, SUDIPTO; DEY, PRADIP; SINGH, PRIYA; BHARDWAJ, SHASHANK SINGH; SEN, DHIMAN; BOSE, ARJIT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
A 36-year-old lady, with unfortunate history of Medical termination of Pregnancy 1 month back, presented with alleged history of 400 mL of agricultural herbicide glyphosate ingestion 18 h back. On complete evaluation, she was found to have acute kidney injury with hyperkalemia, acute liver injury, respiratory depression, and myocardial depression. She was treated conservatively with IV fluids, IV antibiotics, IV calcium gluconate and insulin-dextrose, and IV noradrenaline and was put under invasive ventilation. Continuous renal replacement therapy was started along with toxin removal cartridge HA230. She improved dramatically and had complete recovery within 3 days and has now returned to her normal life.